2019
DOI: 10.3389/fendo.2019.00350
|View full text |Cite|
|
Sign up to set email alerts
|

Thyroid Hormone Action on Innate Immunity

Abstract: The interplay between thyroid hormone action and the immune system has been established in physiological and pathological settings. However, their connection is complex and still not completely understood. The thyroid hormones (THs), 3,3′,5,5′ tetraiodo-L-thyroxine (T4) and 3,3′,5-triiodo-L-thyronine (T3) play essential roles in both the innate and adaptive immune responses. Despite much research having been carried out on this topic, the available data are sometimes difficult to interpret or even contradictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 107 publications
6
79
0
Order By: Relevance
“…It is important to determine thyroid hormone activities and immune responses [27]. The addition of RHP (1 or 2%) to the growing rabbit diet enhanced thyroid function and immune responses, which reflected on rabbit growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine thyroid hormone activities and immune responses [27]. The addition of RHP (1 or 2%) to the growing rabbit diet enhanced thyroid function and immune responses, which reflected on rabbit growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative evidence reveals that thyroid hormones can exert responses on diverse immune cells that affect several inflammation-related processes (such as chemotaxis, phagocytosis, generation of reactive oxygen species, and cytokine production) [5]. Thus, interactions between the endocrine and immune systems contribute to pathological conditions, including viral infections.…”
Section: Levothyroxine Therapymentioning
confidence: 99%
“…For example, both neutrophils and DC express T3 (the active form of TH) transporters (MCT10 in human) and type 2 and 3 deiodinases (involved in THs synthesis) ( 84 86 ). Indeed, it has been widely demonstrated that THs interact with hematopoietic cells ( 85 90 ) at different levels. T3 might affect target immune cells by binding both to nuclear receptors (thyroid hormones receptors TRα and TRβ) and membrane receptors ( 86 90 ).…”
Section: The Link Between Leukocytes and Thyroid Hormonesmentioning
confidence: 99%
“…T3 might affect target immune cells by binding both to nuclear receptors (thyroid hormones receptors TRα and TRβ) and membrane receptors ( 86 90 ). For example, TH and especially T3 can influence maturation of DCs ( 84 , 85 ). DC phenotype was studied in thyroidectomized patients before and after levothyroxine supplementation, showing that THs induce an increase in DCs number and influence their functions ( 91 ).…”
Section: The Link Between Leukocytes and Thyroid Hormonesmentioning
confidence: 99%